ICTIOFAUNA DA REBIO CÓRREGO GRANDE E SEU ENTORNO: COMUNIDADES E CONSERVAÇÃO DOS AMBIENTES AQUÁTICOS - Guimaraes, Felipe Vieira (2020)
Abstract: In the state of Espírito Santo, only 11% of its original Atlantic Forest remains, in the form of small remnants, including the Córrego Grande Biological Reserve, which features headwaters and small tributaries of the Itaúnas Ri